PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM BERBANTUAN GOOGLE SITES UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPS - WARYANA WARYANA (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2021)
The objectives to be achieved in this study are: (1) To find out whether the application of the Google Sites-Assisted Flipped Classroom learning model can increase student learning activity in the Social Sciences subject for class VIIIA semester 1 of Veteran 1 Manyaran Middle School in the 2021/2022 academic year. (2) To find out whether the Flipped Classroom Learning Model Assisted by Google Sites can improve the learning outcomes of SMP Class VIIIA students in social studies subjects. This research is expected to be useful: (1) For teachers as input on the use of the Google Sites-Assisted Flipped Classroom Learning Model in social studies learning to increase student learning activity, (2) For students, it is expected to increase activeness and learning outcomes in social studies subjects. The results showed that the application of the Google Sites-Assisted Flipped Classroom learning model was able to increase student activity from the pre-cycle learning activity percentage of 31%, increasing in cycle 1 to 75%, and in cycle 2 to 94%. That the Flipped Classroom Learning Model Assisted by Google Sites is able to improve student learning outcomes from an average of 72.50 in the pre-cycle to an average of 75.63 in cycle 1 and 80.63 in cycle 2. In the end, the researcher hopes that the results of this classroom action research can be used by teachers as an alternative in learning to increase student interest and learning outcomes in social studies in particular, and all subjects in general. ABSTRAKTujuan yang akan dicapai dalam penelitian ini adalah: (1) Untuk mengetahui apakah penerapan model pembelajaran Flipped Classroom Berbantuan Google Sites dapat meningkatkan keaktifan belajar siswa pada mata Pelajaran IPS kelas VIIIA semester 1 SMP Veteran 1 Manyaran Tahun Pelajaran 2021/2022. (2) Untuk mengetahui apakah Model Pembelajaran Flipped Classroom Berbantuan Google Sites dapat meningkatkan hasil belajar siswa SMP Kelas VIIIA dalam mata pelajaran IPS. Penelitian ini diharapkan dapat bermanfaat: (1) Bagi guru sebagai bahan masukan tentang penggunaan Model Pembelajaran Flipped Classroom Berbantuan Google Sites dalam pembelajaran IPS untuk meningkatkan keaktifan Belajar belajar siswa, (2) Bagi siswa diharapkan dapat meningkatkan keaktifan dan hasil belajar pada mata pelajaran IPS. Hasil Penelitian menunjukkan bahwa penerapan model pembelajaran Flipped Classroom Berbantuan Google Sites mampu meningkatkan keaktifan siswa dari prosentase keaktifan belajar pra siklus sebesar 31 % meningkat pada siklus 1 menjadi 75 %, dan pada siklus 2 menjadi 94 %. Bahwa Model pembelajaran Flipped Classroom Berbantuan Google Sites mampu meningkatkan hasil belajar siswa dari rata-rata 72,50 pada pra siklus menjadi rata-rata 75,63 pada siklus 1 dan 80,63 pada siklus 2. Pada akhirnya peneliti berharap hasil penelitian tindakan kelas ini dapat digunakan oleh para guru sebagai salah satu alternatif dalam pembelajaran untuk meningkatkan minat dan hasil belajar siswa dalam pelajaran IPS khususnya, dan semua mata pelajaran pada umumnya.